Profile of Sustainability Awareness at Elementary School Bumirejo 2 Kebumen - Suhadi, Ahmad; Ramadani, Novita; Parwati, Ade Ayu; Pamungkas, Gesti Anggraeni; Nafingudin, Moh.; Amrissadiah, Nurul Aulia; Billa, Zahro Adha Zamzam; Safitri, Iin Nur; Fatimah, Siti; Fauziah, Muna; Rinawati, Atim; Wardopo, Komper; et al. (Proceeding International Conference on Religion, Science and Education, 2025)
Sustainability awareness is the understanding and awareness of individuals or groups regarding the process of sustainable development and the impact of their actions on the surrounding environment. The purpose of this study was to analyze the profile of students’ sustainability awareness at Elementary School 2 Bumirejo, Kebumen related to energy material. This study was a survey study. The subjects of this study were 25 4th grade students. The data collection technique used a semi-closed questionnaire. The data analysis technique used a descriptive technique which aims to provide a clear and detailed description of the data that has been collected which then makes it easier to interpret and make decisions based on the existing data . The results of the analysis showed that students’ sustainability awareness was included in the good category, with an average score of 73.06%. The Emotional Awareness (EA) category is the highest category compared to other categories, with a percentage score of 85%. Meanwhile, the sustainability practice awareness (SPA) category is the lowest category compared to other categories, with a percentage score of 60.8%. These results indicate that the research conducted has supported the concept of Educational for Sustainability Development (ESD) at the sustainability awareness level.